Liability of Parking Management for Consumer Vehicles Loss in Parking Facilities: (A Case Study of the Supreme Court of Indonesia Decision No. 2078K/Pdt/2009) - Okhtiara, Farizka; Joesoef, Iwan Erar (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
This study aims to analyze the legal liability of parking operators for the loss of consumers’ vehicles within parking areas, with specific reference to Supreme Court Decision No. 2078K/Pdt/2009. The research examines the legal nature of parking arrangements, the validity of exculpatory clauses printed on parking tickets, and the extent of the operator’s responsibility under Indonesian civil law and consumer protection law. Using a normative juridical method supported by a statutory and case approach, this study identifies the parking agreement as a deposit contract, thereby imposing a legal obligation on operators to safeguard and return the vehicle entrusted to them. The findings reveal that any exculpatory clause that shifts liability to consumers is null and void pursuant to Article 18 of the Consumer Protection Law. The Supreme Court decision further confirms that liability for vehicle loss arises from the operator’s failure to provide adequate supervision and security. The research concludes that parking operators bear strict responsibility for securing vehicles within their premises and must implement appropriate risk-management measures, including the use of insurance. These conclusions reinforce the need for enhanced consumer protection standards and clearer operational obligations within parking services.